The impact of low-carbon city pilot policy on carbon emission intensity: evidence from China using a multi-period difference-in-differences model - Shu, Jia-Xian; Peng, Jia-Jia; Zhang, Jing (Frontiers in Environmental Science, 2025)
In the context of global efforts to combat climate change, highlighted by the 2024 UN Climate Change Conference (COP29) and the growing global emphasis on low-carbon development, this study investigates the impact of China’s low-carbon city pilot policies on carbon emission intensity. Using data from 283 Chinese cities between 2005 and 2021, a multi-period difference-in-differences (DID) model is employed to analyze the effects of these policies. The study also explores the mediating mechanisms, moderating effects, and heterogeneity across cities. The main findings are as follows: (1) The low-carbon city pilot policies significantly reduce carbon emission intensity, with the impact becoming stronger and more stable over time. (2) The reduction in carbon intensity is partially mediated by enhanced carbon sink levels and industrial structure upgrades, although technological investment does not have a significant effect. (3) Environmental regulations negatively moderate the policy’s effectiveness, while fiscal freedom and population growth rates positively influence its impact. (4) The effects of the policy are heterogeneous across cities, driven by differences in economic levels, geographical locations, industrial bases, resource endowments, and population sizes. This paper provides valuable empirical insights and policy recommendations for China’s low-carbon transition and for achieving its carbon neutrality and peak emission targets.